The Development of Endoscopic Techniques for Treatment of Walled-Off Pancreatic Necrosis: A Single-Center Experience - Mateusz Jagielski; Marian Smoczyński; Anna Jabłońska; Krystian Adrych (Gastroenterology Research and Practice)
Background. Endotherapy is a common method of treatment in patients with symptomatic walled-off pancreatic necrosis (WOPN). The aim of this study is to indicate the potential therapeutic possibilities created by the combination of several new endoscopic techniques and the evaluation of their efficacy in the treatment of WOPN. Methods. The retrospective analysis of results and complications in the group of 101 patients, who underwent endoscopic treatment of symptomatic WOPN between years 2011 and 2015. Results. Endoscopic treatment was started in 101 patients (71 men, 30 women; mean age 50.97 years) with symptomatic WOPN. Single transluminal gateway technique (SGT) was used in 93/101 (92.08%) patients. SGT in combination with multiple transluminal gateway technique (MTGT) was exploited in 4/93 (4.30%) patients, while in combination with single transluminal gateway transcystic multiple drainage (SGTMD) in 22/93 (23.66%) patients. Transpapillary access was used in 11/101 (10.89%) patients. 20/101 (19.80%) patients underwent percutaneous drainage. Fluoroscopy-guided endoscopic necrosectomy was performed in 19/101 (18.81%) patients. The combinations of endoscopic techniques depended on the extent of necrosis. Procedure-related complications occurred in 16/101 (15.84%) patients. The mortality rate was 0.99% (1/101 patient). Therapeutic success was achieved in 99/101 (98.02%) patients. The long-term success of endoscopic treatment was achieved in 97/101 (96.04%) patients with symptomatic WOPN. Conclusions. Application of new endoscopic techniques in the treatment of the patients with symptomatic WOPN significantly improves the efficiency of endotherapy with an acceptable amount of complications.